2022
DOI: 10.1093/rap/rkad027
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced granulomatosis with polyangiitis—an under-recognized condition

Abstract: Objectives Cocaine and cocaine mixed with levamisole are increasingly used in the UK and result in significant direct nasal damage in addition to promoting vasculitis. Our aims were as follows: (1) to identify the main symptoms and presentation of cocaine-induced vasculitis; (2) to provide evidence regarding the best practice for the investigation and diagnosis of cocaine-induced vasculitis; and (3) to analyse the clinical outcomes of patients in order to understand the optimal management for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…This is perhaps shown indirectly by the observation that the number of included patients in published case series is growing. Granulomatosis with polyangiitis and microscopic polyangiitis affect men and women equally, which was also the case in this study on cocaine-induced vasculitis [ 5 ]. A higher prevalence in men has been reported previously [ 2 ], but it should be noted that men are more likely to use cocaine [ 1 ].…”
supporting
confidence: 66%
See 2 more Smart Citations
“…This is perhaps shown indirectly by the observation that the number of included patients in published case series is growing. Granulomatosis with polyangiitis and microscopic polyangiitis affect men and women equally, which was also the case in this study on cocaine-induced vasculitis [ 5 ]. A higher prevalence in men has been reported previously [ 2 ], but it should be noted that men are more likely to use cocaine [ 1 ].…”
supporting
confidence: 66%
“…It is a clinical challenge for rheumatologists, nephrologists, pulmonologists, dermatologists and ENT specialists to differentiate a cocaine-induced vasculitis from AAV. In this issue of Rheumatology Advances in Practice , Gill et al [ 5 ] were able to carry out retrospective analysis of a large number of patients who presented during a 5-year period in tertiary centres in London and Birmingham. In total, 42 patients with severe nasal damage mimicking AAV were included who disclosed cocaine use or had positive urine toxicology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Nonetheless, the inverse association we observed in our p-ANCA patients (PR3 + MPO-) is not novel and corroborates previous findings showing that p-ANCA pattern is the most common pattern in CIMDL patients 5,29 with up to 57% of them being PR3 + . 20,30 In a recent large case series conducted in the United Kingdom, which included 42 patients with CIMDL and vasculitis compatible with GPA, Gill and colleagues 31 found that only 29% of their patients had a p-ANCA pattern with PR3+, a lower percentage that could have been influenced by the inclusion of patients with GPA (c-ANCA PR3+). In one of the largest case series of LIV, patients showed a clear predominance of p-ANCA pattern (93%) which, however, was directed against both PR3 and MPO (PR3 + MPO+) in 57% of cases or against MPO alone (PR3-MPO+) in the remaining ones, whereas isolated c-ANCA or isolated PR3 positivity was less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…105,106 The presence of NETs has been detected in several typical lesion sites, including the kidney, skin, and thrombus of individuals with AAV. 107 Specifically, NETs have been recognized in the neuropathy of individuals with AAV, while they are absent in patients with nonvasculitic demyelinating neuropathy. 108 Some studies demonstrated an overall increase in NETosis in patients with active vasculitis, along with the presence of fragmented NETs in affected tissues and the bloodstream of AAV patients.…”
Section: Nets In Anca-associated Vasculitis (Aav)mentioning
confidence: 99%